The role of the Physical Education and Sports Sessions in Developing Middle School Students' Health awareness -From Setif State Teachers' and Inspectors' Point of View - HAZEM , ABDERREZAK; SAOUDI, DJENIDI (sports creativity, 2023)
the study aims to find out the extent to which the current reforms in the educational system of physical and sports education meet the level of health awareness in the light of the application of second-generation curricula among middle-school students, through its outputs represented in the qualitative health education of the student and its proven effectiveness at several levels in terms of combating psychological pests and diseases at several levels after the formation and development of conscious and applied healthy behavior. The study was conducted on 20 teachers of Intermediate Education and 05 inspectors of the subject in the state of Setif. to reach results, two questionnaires were built with four axes within the descriptive curriculum (school survey), which was adopted for the study. after collecting the information, it was treated with the (Spss 20) program. the study reached a number of results, the most important of which is physical and sports education is one of the basic school building blocks. it also works to acquire new patterns of thinking and healthy behavior. awareness of physical health and the health of internal functional organs such as the respiratory, circulatory and others play an important role in Psychological Rehabilitation and sports are not limited to the development of the body, but also contribute to the treatment of Anxiety and fear disorders, mood disorders or emotional and social disorders with peers, as well as mental disorders that negatively affect the perception and personality building of the pupil. Keywords: physical and sports education; health awareness; Middle School Students'